Differential and linear properties analysis of the ciphers rijndael, serpent, threefish with 16-bit inputs and outputs - Лисицкая, Ирина Викторовна; Гриненко, Татьяна Алексеевна; Бессонов, Станислав Юрьевич (Eastern-European Journal of Enterprise Technologies, 2015)
The results of the differential and linear properties analysis of the ciphers Rijndael, Serpent, Threefish with 16-bit input and output data blocks, indicating that all the ciphers repeat the properties of random permutations in the considered application mode are presented. The main provisions of a new methodology for accelerated cryptanalysis of block symmetric ciphers to the linear and differential cryptanalysis attacks consisting in the fact that all modern block ciphers after a certain number of cycles under the laws of transition distribution of XOR difference tables (total differentials) and the laws of bias of XOR difference tables (total differentials) repeat the corresponding indexes of random permutations are confirmed. The testing of randomness indexes of large ciphers can be accomplished through the development and subsequent analysis of randomness indexes of reduced models that allow carrying out real-time computational experiments. The results are further evidence that the full-scale ciphers and their small versions asymptotically repeat properties of random permutations of the corresponding degree.